Construction of a chromosome 17 transcriptome in serous ovarian cancer identifies differentially expressed genes. Issue 5 (1st August 2008) - Wojnarowicz, P. M.; Breznan, A.; Arcand, S. L.; Filali-Mouhim, A.; Provencher, D. M.; Mes-Masson, A.-M.; Tonin, P. N.
Abstract : Cytogenetic, molecular genetic, and functional analyses have implicated chromosome 17 genes in epithelial ovarian cancer (EOC). To further characterize the contribution of chromosome 17 genes in EOC, the Affymetrix U133A GeneChip was used to perform transcriptome analyses of 15 primary cultures of normal ovarian surface epithelial (NOSE) cells and 17 malignant ovarian tumor (TOV) samples of the serous histopathologic subtype. A two-way comparative analysis of 776 known genes and expressed sequences identified 253 genes that exhibited at least a threefold difference in expression in at least one TOV sample compared to the mean of NOSE samples. Within this data set, 99 of the 253 (39.1%) genes exhibited similar patterns of expression across all tested samples, suggesting a high degree of concordance in the chromosome 17 transcriptome. This observation was supported by hierarchical clustering analysis that segregated the TOV and NOSE samples into two separate groups. There were 77 genes that were differentially expressed in at least 50% of the TOV samples. Five genes ( AdoRA2B at 17p12, CCL2 at 17q12, ACLY at 17q21.2, WIPI1 at 17q24.2, and SLC16A3 at 17q25.3) were significantly ( P < 5.13E−11) differentially expressed at least threefold in all serous TOV samples, and all five genes were underexpressed in these TOV samples as compared to the NOSE samples. Interestingly, several of these differentially expressed genes have been previously associated with response to hypoxia.